(untitled) (MAUSAM, 2010)
AMDAR observations from Lufthansa and Lufthansa cargo aircrafts in BUFR format (with header IUADOI EGGR and IUAHOI EGRR) were made available to India Meteorological Department (IMD) and in turn to National Centre for Medium Range Weather Forecasting (NCMRWF) under special arrangement for a period of two weeks w.e.f. 14th May 2008. These data have been assimilated at NCMRWF (National Centre for Medium Range Weather Forecasting) model for the period 14th - 31st May, 2008 to assess its impact on NWP. Use of these observations gave some positive impact on NWP systems.